Edekuasi Perlindungan Hukum Tenaga Medis Dalam Perspektif Hukum Kesehatan Indonesia - Sri Yati; Chandra Suryati (Yayasan Inspirasi El Burhani, 2026)
Introduction: Medical personnel play a vital role in the healthcare system and face increasing legal risks, including malpractice claims, criminal accusations, ethical sanctions, and workplace violence. In Indonesia, legal protection is regulated under Law Number 29 of 2004 concerning Medical Practice and Law Number 17 of 2023 concerning Health. However, the implementation of these protections remains insufficient, as indicated by the rising number of violence and legal disputes involving healthcare workers. Objective: This study aims to analyze the construction of legal protection for medical personnel in Indonesia and examine the role of legal education as a preventive strategy to strengthen such protection. Method: This study employed a normative juridical method using statutory and conceptual approaches. Data were analyzed qualitatively through the review of national regulations, legal theories, and international literature related to medical liability, workplace violence, patient safety, and legal literacy in healthcare practice. Result: The findings indicate that violence against medical personnel in Indonesia increased during 2023–2025, including physical violence, verbal abuse, bullying, and intimidation. Existing legal protection mechanisms remain more repressive than preventive. Legal education was found to enhance healthcare workers’ understanding of professional rights, informed consent, medical documentation, and dispute prevention. Limited legal literacy contributes to the risk of medical criminalization and defensive medicine practices. The study also identified implementation strategies such as integrating health law into professional curricula, continuous legal training, medical dispute simulations, and collaboration with legal aid institutions. Conclusion: Legal protection for medical personnel requires not only adequate regulations but also sustainable legal education. Strengthening legal literacy can reduce malpractice risks, improve professional accountability, prevent medical criminalization, and support patient safety within Indonesia’s healthcare system.